Estimated timing of the first menstrual period and dietary and nutritional correlates of menarche among urban school-going adolescents in four sub-Saharan African sites - Costa, Janaína Calu; Darling, Anne Marie; Shinde, Sachin; Tadesse, Amare W.; Sherfi, Huda; Mwanyika-Sando, Mary; Tinkasimile, Amani; Sharma, Deepika; Bärnighausen, Till; Fawzi, Wafaie W. (Maternal & child nutrition, 2025)
Characterizing the timing of menarche and the factors that are associated with it is important for understanding a population's reproductive health needs and long-term health trajectories. We estimated the age at the menstrual onset among adolescent girls and the association between dietary and nutritional factors and menarche in four sub-Saharan African urban sites. We used cross-sectional school-based data from 2307 female adolescents aged 10-14 years collected by the Africa Research, Implementation Science, and Education (ARISE) Network in Ouagadougou, Burkina Faso; Addis Ababa, Ethiopia; Khartoum, Sudan; and Dar es Salaam, Tanzania. Logit models were used to estimate the median age at menarche at each site. Associations between menarche and BMI-for-age, stunting, dietary quality and food insecurity across settings were assessed using Poisson regression models adjusted for country and school levels. The estimated median age at menarche was 13.1 years (95% confidence interval: 12.7, 13.5) in Ouagadougou; 12.9 (12.6, 13.2) in Addis Ababa; 13.3 (12.7, 13.6) in Khartoum; and 13.2 (12.3, 14.0) in Dar es Salaam. Between 18% and 49% of the girls in each setting had already menstruated. Based on the pooled multivariable models, underweight participants were 42% less likely (adjusted prevalence ratio [PR] 0.58 [0.44, 0.77]) to have experienced menarche in comparison to normal-weight individuals. The likelihood of experiencing menarche increased for overweight [PR 1.47 (1.30,1.66)] and obese [PR 1.57 (1.35,1.82)] in comparison to normal-weight girls. Those stunted were 47% less likely to have experienced menarche [PR 0.53 (0.41, 0.69)] than their nonstunted counterparts. A lower likelihood of menarche among those experiencing moderate/severe hunger when compared to those with no/little hunger was also observed (PR 0.78 [0.63,0.96]). No evidence of association with dietary quality was found. Further research is needed to strengthen the body of evidence and inform evidence-based initiatives in low- and middle-income settings.